Penerapan Performance-based zoning dalam Penataan Ruang Laut: Suatu Tinjauan Teoretis - Putu Oktavia (Institut Teknologi Sains Bandung, 2023)
One of the last innovations in techniques to control space use by zoning regulation is performance-based zoning. In a regulatory system, performance-based zoning seek to allow or prohibit an activity or use of space based on a series of criteria that show performance of the activities or the use of space, or certain performance standards set for the zone and use. Large body of scholar state the potential application of performance-based zoning in ocean spaces. This paper aim to examine the possibility of applying performance zoning as a form of control in the utilization of sea space. Data obtained from secondary sources such as reports and related studies. Based on literature, the application of performance-based zoning in sea space provides many advantages as well as challenges. Performance-based zoning seeks to contain the impact from a use or activity, rather than restricting the use or activity in a zone as long as that activity follows a standard or specific target. Performance-based zoning only separate certain use of space from other uses only if the use had a negative impact on the surrounding environment, therefore reducing the need to establish definitive boundaries between uses. However, there is a possibility that, because of many things that must be considered in the measurement of performance, a number of specific impacts might be failed to consider